Geographical analysis of the Pacific and Atlantic Oceans in the Americas: A comparative Study of Tidal Energy Potential - Espinoza Fadua; Parada María (E3S Web of Conferences)
Tidal energy offers a promising renewable energy source, leveraging predictable oceanic forces to generate electricity. However, the potential for tidal energy varies significantly across regions due to geographical and oceanographic factors. This study explores the geographical and oceanographic factors that influence tidal energy potential along the coasts of the Pacific and Atlantic Oceans in the Americas. By leveraging mathematical modelling and empirical data analysis, the research identifies key regions with significant tidal energy generation potential. Results highlight the Bay of Fundy in the Atlantic, with tidal amplitudes of up to 15 meters supporting 1000 MW of potential energy using horizontal-axis turbines. In the Pacific, the Chacao Channel demonstrates stable currents of 2.8 m/s, offering a potential of 200 MW using bulb turbines. This research underscores the importance of tailoring energy technologies to local conditions to enhance renewable energy adoption.